The Role of School Committees and Associations in Supporting Competitive Advantage in Muhammadiyah Elementary School 2 Krian: Peran Komite Sekolah dan Paguyuban dalam Mendukung Keunggulan Bersaing di Sekolah Dasar Muhammadiyah 2 Krian - Fahrur, Amam; Haryanto, Budi (Universitas Muhammadiyah Sidoarjo, 2023)
This research is a case study research because the focus of this research is to answer the question